The thesis writing journeys of bachelor's and master's students : a transnational European perspective - Petrić, Bojana; Castelló, Montserrat, 1960- (Bristol, UK ; Jackson, TN : Multilingual Matters, 2025)
"This book explores the student experience of thesis writing through an interdisciplinary perspective drawing on theories of learning, emotions, and genre and narrative/discursive analysis. As a result of this approach, the thesis is reconceptualised as a multilayered experience from the point of view of student writers"--
Bachelor's and master's thesis writing : a research agenda / Bojana Petrić and Montserrat Castelló -- Investigating bachelor's and master's thesis writing : the research context and methodology of the project / Montserrat Castelló, Bojana Petrić and Christiane Donahue -- Kari's thesis writing journey : 'This thesis I did myself' / Kristin Solli -- Andrada's thesis writing journey : 'My professor guided me' / Claudia Doroholschi -- Interview-based research in multilingual research situations : issues and challenges in the context of publishing in English / Natalie Schembri and Alma Jahić Jašić -- How thesis writers speak about their experiences : a linguistic perspective / Tatyana Yakhontova and Mira Bekar -- Re-constructing the emotional process of writing master's and bachelor's theses / Crista Weise and Montserrat Castelló -- "The material you're working with is yourself" : student learning experiences with thesis writing / Claudia Doroholschi and Kristin Solli -- Writing a master's thesis : challenges and coping strategies / Alma Jahić Jašić and Tanja Pavlović -- Doing the literature review of a master's/bachelor's thesis : students' understandings and practices / José Brandão Carvalho, Tatyana Yakhontova, Luísa Álvares Pereira and Luciana Graça -- Students' thesis writing experiences : conclusions, implications and ways forward / Bojana Petrić and Montserrat Castelló -- Afterward : some observations / Charles Bazerman.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Academic writing -- Europe; Dissertations, Academic -- Europe; College students -- Europe; Thèses et écrits académiques -- Europe; Étudiants -- Europe; EDUCATION / Adult & Continuing Education